Feasibility of using administrative data for identifying medical reasons to delay hip fracture surgery: a Canadian database study. Issue 10 (5th October 2017) - Guy, Pierre; Sheehan, Katie J; Morin, Suzanne N; Waddell, James; Dunbar, Michael; Harvey, Edward; Sirett, Susan; Sobolev, Boris; Kuramoto, Lisa; Tang, Michael
Abstract : Purpose: Failure to account for medically necessary delays may lead to an underestimation of early surgery benefits. This study investigated the feasibility of using administrative data to identify the National Institute for Health and Care Excellence (NICE) 124 guideline list of conditions that appropriately delay hip fracture surgery. Methods: We assembled a list of diagnosis and procedure codes to reflect the NICE 124 conditions. The list was reviewed and updated by an advanced clinical coder. The list was refined by five clinical experts. We then screened Canadian Institute for Health Information discharge abstracts for 153 918 patients surgically treated for a non-pathological first hip fracture between 1 January 2004 and 31 December 2012 for diagnosis codes present on admission and procedure codes that antedated hip fracture surgery. We classified abstracts as having medical reasons for delaying surgery based on the presence of these codes. Results: In total, 10 237 (6.7%; 95% CI 6.5% to 6.8%) patients had diagnostic and procedure codes indicating medical reasons for delay. The most common reasons for medical delay were exacerbation of a chronic chest condition (35.9%) and acute chest infection (23.2%). The proportion of patients with reasons for medical delays increased with time from admission to surgery: 3.9% (95% CI 3.6% to 4.1%) for same day surgery; 4.7% (95% CI 4.5% to 4.8%) for surgery 1 day after admission; 7.1% (95% CI 6.9% to 7.4%) for surgery 2 days after admission; and 15.5% (95% CI 15.1% to 16.0%) for surgery more than 2 days after admission. The trend was seen for admissions on weekday working hours, weekday after hours and on weekends. Conclusion: Administrative data can be considered to identify conditions that appropriately delay hip fracture surgery. Accounting for medically necessary delays can improve estimates of the effectiveness of early surgery.